(Self) Critical Pedagogy: Performing Vulnerability to Teach STS in Singapore - Monamie Haines (Engaging Science, Technology, and Society)
As more and more STS positions open in different regions of the world, there is an increased transnational migration of scholars trained in one part of the world working in another. Yet, there is often little guidance for scholars on how to negotiate their positionalities in different cultural, political, and pedagogical expectations. In this essay, I reflect upon my three years at a major Singaporean institution of higher learning, teaching STS and social theory, by discussing how I articulated a fragmented identity and performed vulnerability through my different intersubjective roles—researcher, educator, mother, employer, Indian, American—to model the kind of critical thinking I wished my students to undertake. I focus on negotiating my American political sensibilities in the Singaporean context, when trying to teach race and technology in Singapore.